Commentary on the role of expert opinion in developing evidence‐based guidelines. (22nd October 2013) - Eibling, David; Fried, Marvin; Blitzer, Andrew; Postma, Gregory
<x xml:space="preserve">Abstract</x> Evidence‐based clinical practice guidelines (CPGs) help guide busy practitioners in clinical decision making. CPGs are evidence‐based in that recommendations are based on available knowledge derived from published clinical trials. The challenges presented by the tasks of finding, assessing, interpreting, and assembling the information in these reports are herculean. Missing or imperfect evidence may lead to the publication of suboptimal guidelines, even when the other components of the development process have been flawlessly performed. This commentary highlights the requirement that expert opinion must be explicitly recognized by CPG authoring groups when the published evidence is missing or inadequate. Laryngoscope, 124:355–357, 2014